Could Prolonged Usage of GPS Navigation Implemented in Augmented Reality Smart Glasses Affect Hippocampal Functional Connectivity? - Fajnerová, Iveta; Greguš, David; Hlinka, Jaroslav; Nekovářová, Tereza; Škoch, Antonín; Zítka, Tomáš; Romportl, Jan; Žáčková, Eva; Horáček, Jiří (BioMed research international, 2018)
BACKGROUND: Augmented reality (AR) glasses with GPS navigation represent the rapidly evolving technology which spares (and externalizes) navigational capacities. Regarding the expected everyday usage of this device, its impact on neuroplastic brain changes and navigation abilities should be evaluated. AIMS: This study aimed to assess possible changes in functional connectivity (FC) of hippocampus and other brain regions involved in spatial navigation. METHODS: Thirty-three healthy participants completed two resting state functional magnetic resonance imaging (rsfMRI) measurements at the baseline and after 3 months. For this period, the experimental group (n = 17) has had used AR device (Vuzix M100) with incorporated GPS guidance system during navigation in real world. Participants from the control group (n = 16) have not used any GPS device while navigating during walking. The rsfMRI FC of right and left hippocampi was analyzed using a seed-driven approach. Virtual city task was used to test navigational abilities both before and after the usage of AR device. RESULTS: We identified strong functional coupling of right and left hippocampi at the baseline (p < 0.05, FDR corrected). Mild changes in bilateral hippocampal FC (p < 0.05, FDR uncorrected) were observed in both assessed groups mainly between the bilateral hippocampi and between each hippocampus and temporal regions and cerebellum. However, the experimental group showed FC decrease after three months of using GPS navigation implemented in AR glasses in contrast to FC increase in the control group without such intervention. Importantly, no effect of intervention on navigational abilities was observed. DISCUSSION: Our observation supports the assumption that externalization of spatial navigation to technological device (GPS in AR glasses) can decrease the functional coupling between hippocampus and associated brain regions. Considering some limitations of the present study, further studies should elucidate the mechanism of the observed changes and their impact on cognitive abilities.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; Cerebellum; Humans; Spatial Navigation; geografické informační systémy; Female; Temporal Lobe; dospělí; spánkový lalok; Hippocampus; lidé; Virtual Reality; hipokampus; Adult; ženské pohlaví; Male; virtuální realita; Geographic Information Systems; mozeček; prostorová navigace; mužské pohlaví